Incomplete, stable-like, peri-prosthetic Vancouver B fracture around an ha-coated stem. Is there a case for strategic thoughtful neglect?. (December 2019) - Spina, Mauro; Scalvi, Andrea; Vacchiano, Andrea; Sandri, Andrea; Balsano, Massimo
Abstract: The Periprosthetic fracture of the proximal femur is usually treated by internal fixation of the fracture or revision of the femoral stem depending on the characteristics of the fracture and stability of the implant. This case report shows an early periprosthetic fracture around an uncemented straight stem which is treated conservatively with an excellent clinical radiographic result and explains the biomechanics related to this non-operative choice. A conservative treatment of periprosthetic fracture is possible but only after a careful analysis of the fracture pattern, the characteristics of the prosthetic stem and the time elapsed from implanting the prosthesis to the fracture.